Behavioral Determinants of Leadership Engagement in Health Profession Students: A Cross-Sectional Study Using the Theoretical Domains Framework (TDF) - Alla El-Awaisi (13987947) (2025)
Introduction Leadership is a critical competency in healthcare, influencing patient outcomes, organizational performance, and interprofessional collaboration. The study aimed to explore the behavioral determinants of leadership engagement among health profession students, and to examine associations with sociodemographic characteristics and leadership experience. Methods A cross-sectional survey was administrated to health profession students at Qatar University health sector (n= 225). The survey was developed using the Theoretical Domains Framework (TDF) and analyzed using principal component analysis (PCA) to identify key behavioral components. Ordinal regression was used to assess associations between the components and sociodemographic factors, including nationality, college affiliation, and prior and current leadership experience. Results PCA identified four behavioral determinants of leadership: 1) intention and self-efficacy, 2) awareness of opportunities, 3) perceived benefits, and outcomes, and 4) perceived barriers, each demonstrating acceptable internal consistency. Regression analysis confirmed significant predictive power across these determinants, with factors such as college affiliation, nationality, and prior leadership experience influencing outcomes. Approximately 25% of students reported holding leadership roles, yet more than half of these student leaders had no formal leadership training. Discussion Findings highlight the importance of integrating structured leadership training and increasing access to leadership opportunities in a diverse, interprofessional student population. Initiatives such as interprofessional education student associations provide a valuable platform for fostering leadership skills in collaborative settings. These findings can inform the design of targeted educational interventions that support the development of essential leadership skills and cultivate the next generation of health leaders. Other Information Published in: Journal of Healthcare Leadership License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/jhl.s525278